Joyful Learning as a Method in Improving Students' Self-Efficacy in the Learning Process of Islamic Education at SMPN 2 Palangka Raya - Norheni Aulia; Surawan Surawan (Indonesian Journal of Islamic Education and Learning, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students to become religious and morally upright individuals. However, the learning process of PAI at SMPN 2 Palangka Raya still faces challenges, particularly the low level of students' self-efficacy, which is reflected in their reluctance to express opinions, feelings of inferiority, anxiety, and lack of motivation. One of the contributing factors is the use of monotonous and unengaging teaching methods. This study aims to analyse the effectiveness of the Joyful Learning method in enhancing students’ self-efficacy in PAI learning. The research employed a quantitative approach with descriptive analysis. The results showed that the implementation of Joyful Learning at SMPN 2 Palangka Raya successfully created a pleasant, interactive, and supportive learning environment. This strategy encouraged students to participate actively, feel appreciated, and express themselves without fear, thereby increasing their confidence and belief in their own abilities (self-efficacy). Thus, Joyful Learning proves to be an effective method in supporting PAI learning and in fostering more confident and motivated students.